New insights into the phylogeny of Laelapinae mites (Mesostigmata: Laelapidae) associated with sigmodontine rodents (Cricetidae) from Argentina, with a morphological characterization of two species of Mysolaelaps Fonseca, 1936 - Savchenko, Ekaterina; Espinoza-Carniglia, Mario; Lareschi, Marcela (Zootaxa, 2025)
Mites of the subfamily Laelapinae parasitic on small mammals are remarkably diverse in the Neotropics. Within this subfamily, mites of the genus Mysolaelaps Fonseca, 1936 are endemic to the Neotropics and frequently associated with rodents of the tribe Oryzomyini (Cricetidae: Sigmodontinae). Currently, Mysolaelaps comprises three described species, exclusively on the bases of their morphology. This study aimed to provide molecular information of Mysolaelaps microspinosus Fonseca, 1936 and Mysolaelaps parvispinosus Fonseca, 1936 and analyze their phylogenetic relationships to other Laelapinae mites associated with rodents. Thirty-six mites were collected from Oligoryzomys flavescens (Waterhouse, 1837) from Argentina. Among them, 18 mites were identified as M. microspinosus and 18 as M. parvispinosus. A subsample of mites was submitted to DNA extraction and amplification of the nuclear region 18S-ITS1-5.8S-ITS2. The phylogenetic analyses indicated a closer relationship between Mysolaelaps and Laelaps Koch, 1836 than with mites of the genus Androlaelaps Berlese, 1903 and Gigantolaelaps Nesbitt, 1951. The present study highlighted the scarcity of information regarding the molecular biology of the genus Mysolaelaps and the importance of further molecular studies for understanding the evolutionary history of laelapid mites.